Pollination and fruit set behaviour of aonla (Emblica officinalis) - SINGH, H K; SRIVASTAVA, A K; DWIVEDI, R (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted on variability in fruiting potentiality in aonla (Emblica officinalis Gaertn).The maximum tiuit-retention was recorded under open pollination followed by sibbing and geitonogamy, whereas bagging resulted in no-fruit retention. Improvement in fruit retention under sibbing and open pollination compared with the geitonogamy might be due to the effect of foreign pollen grains having high pollination stimulus. Poor-fruit retention under geitonogamy and bagging indicated the possibility of self-incompatility in all the aonla cultivars/genotypes.